Turn-Taking Strategies Produced by Male and Female Presenters in American TV Shows - Nur Trihandayani Rivai (Universitas Gadjah Mada, 2019)
This study aims at examining the turn-taking strategies performed by male presenter, Jimmy Kimmel, and female presenter, Ellen DeGeneres, in two American TV talk shows. The data were analyzed using Stenstrom theory (1994) for the turn-taking strategies performed by both presenters. The findings revealed the following. (1) As the representation of male presenters, in conversation with male guests, Jimmy performed most of the strategies such as hesitant start, clean start, uptakes, links, alert, filled pause/ verbal fillers, silent pause, lexical repetition, a new start prompting and appealing. However, he did not apply metacomment and giving up strategy. Furthermore, in conversation with female guests, he used all the strategies, except hesitant start, metacomment, lexical repetition, a new start, and giving up strategy. (2) As the representation of female presenters, Ellen did not use metacomment, silent pause, and giving up strategies in her conversation with male guests. On the other hand, in conversation with female guests, she used all the strategies, except metacomment strategy. (3) This study also revealed that male presenters interrupted more often to female guests than to male guests, which supports the theory proposed by Zimmerman and West (1975).